Mitotypes Based on Structural Variation of Mitochondrial Genomes Imply Relationships With Morphological Phenotypes and Cytoplasmic Male Sterility in Peppers - Jo, Yeong Deuk; Lee, Hea-Young; Ro, Na-Young; Kim, Sang Hoon; Kim, Jin-Baek; Kang, Byoung-Cheorl; Kang, Si-Yong (Frontiers in Plant Science, 2019)
Plant mitochondrial genomes characteristically contain extensive structural variation that can be used to define and classify cytoplasm types. We developed markers based on structural variation in the mitochondrial genomes of fertile and cytoplasmic male sterility (CMS) pepper lines and applied them to a panel of Capsicum accessions. We designed a total of 20 sequence characterized amplified region (SCAR) markers based on DNA rearrangement junctions or cytoplasm-specific segments that did not show high similarity to any nuclear mitochondrial DNA segments. We used those markers to classify the mitotypes of 96 C. annuum accessions into 15 groups. Precise genotyping of other Capsicum species (C. frutescens, C. chinense, and C. baccatum) was hampered because of various stoichiometric levels of marker amplicons. We developed a multiplex PCR system based on four of the markers that efficiently classified the C. annuum accessions into five mitotype groups. Close relationships between specific mitotypes and morphological phenotypes implied that diversification or domestication of C. annuum germplasm might have been accompanied by structural rearrangements of mitochondrial DNA or the selection of germplasms with specific mitotypes. Meanwhile, CMS lines shared the same amplification profile of markers with another mitotype. Further analysis using mitochondrial DNA (mtDNA) markers based on single nucleotide polymorphisms (SNPs) or insertions and deletions (InDels), and CMS-specific open reading frames (orfs) provided new information about the origin of the CMS-specific mitotype and evaluation of candidates for CMS-associated genes, respectively.